Independent From Cookware Ferromagnetic Characteristics Transferring Maximum Power Each Cookware On Domestic Induction Cooktops - Sinirlioglu, Sercan; Aksoy, Ismail (IEEE, 2016)
In this paper, a control method for each of induction compatible cookwares which have different ferromagnetic characteristics, maximum power that can be transferred safely on the domestic induction cooktops using by end users is presented. The major problem for domestic induction cooktops is cookwares defined as load are various and end users complete the resonant circuit. Five of different ferromagnetic characteristic cookwares are chosen to solve this issue. These cookwares are analyzed with reference coil both with LCR meter and operational status with power mode. Also, mathematical model of power electronic circuit is shown. According to analysis results, minimum safe operating frequency is determined by a method which developed controlling the electrical parameters, for each cookwares. As a result, it is determined that the power transferred to the cookwares is increased and it reaches its maximum point for each cookwares with the help of the new method when it is compared with the current situation.
Keywords: Engineering